Tecnologias digitais no ciclo de alfabetização: uma avaliação sobre a formação de professores na rede municipal de Fortaleza - Nunes, Maria das Graças da Silva (2024)
The present work was developed within the scope of the Professional Master's Degree in Public Policy Assessment (MAPP) with the general objective of evaluating how educational policies for continuing education in the municipal network of Fortaleza are developed for the use of digital technologies in the literacy cycle. To meet this objective, this work was based on normative documents of Brazilian education, such as the National Common Curricular Base – BNCC (2018), Common National Base for Continuing Training – BNC - FC (2020), and Fortaleza, Ordinance 204 /2014, the Ceará Reference Curricular Document – DCRC (2018), a municipal guiding document, in the Guide for the development of digital culture and use of technological resources at school (2022), among others. In order to carry out multidimensional research, this work was based on the perspective of In-Depth Assessment (AP), proposed by Rodrigues (2008); Gussi (2016). The study in question used only the last two axes of In-Depth Assessment: institutional trajectory and temporal and territorial spectrum. Methodologically, this research is qualitative in nature, having adopted bibliographic research, documentary research, non-participant observation and semi-structured interviews as data collection procedures. Data analysis was guided by the content analysis explored by Bardin (2011). The results showed that the Fortaleza education network does not offer training actions for the use of technologies in the literacy cycle. They also demonstrate that teachers recognize the importance of specific training for the pedagogical integration of digital technologies, however the majority stated that they did not receive this training between 2019 and 2023. In view of this, it is recommended that the Municipal Department of Education of Fortaleza implement a targeted training in digital technologies for all teachers in the network, focusing on practice, ensuring adequate infrastructure and encouraging dialogue to understand the training needs of educators.